Analysis of the Setting Agenda of Non-Smoke Areas in Sigi Regency - Siti Hartina; Rizali Djaelangkara; Muh. Rizal S (Universitas Negeri Makassar, 2017)
The purpose of this study was to determine the Agenda Setting Analysis of the establishment of a No Smoking Area Regulation in Sigi District, Analysis Model of Agenda Setting Policy proposed by John Kingdon. This type of research is Descriptive Research and the basis of research used is Qualitative. Informants were determined by purposive sampling with a total of 6 informants. Data collection techniques used are observation, in-depth informal interviews, and documentation to collect the required data in the form of primary and secondary data, triangulation / combined. Research instruments are researchers, a list of questions and supporting tools. Data analysis is done by reducing data, displaying data and drawing conclusions. Purposive or deliberate research location determination. The results of this study indicate that in the process of setting a regulation setting for no-smoking zones in Sigi Regency, it has run well and according to the procedure, while if seen through the results of tracing the three stages of the flow namely problem flow, policy stream, and political stream, the three streams consider problems due to the high smoking users in Sigi Regency and the lack of public awareness of the surrounding health.